The impact of screening on the survival of colorectal cancer in Shanghai, China: a population based study - Xiaopan Li; Yi Zhou; Zheng Luo; Yi'an Gu; Yichen Chen; Chen Yang; Jing Wang; Shaotan Xiao; Qiao Sun; Mengcen Qian; Genming Zhao (BMC, 2019)
Abstract Background Shanghai is one of the earliest cities in developing countries to introduce an organized colorectal screening program for its residents to fight against the rising disease burden of colorectal cancer (CRC). This study aims to investigate the impact of the Shanghai screening program implemented in 2013 on the survival rates of CRC patients. Methods We calculated up to 5-year survival rates for 18,592 CRC patients from a representative district of Shanghai during 2002-2016, using data from the Shanghai Cancer Registry. We performed joinpoint regressions to examine temporal changes in the trends of the CRC survival rates. We then conducted Kaplan-Meier and Cox proportional hazards modelling to study the association of the survival rates with screening behaviors of the patients. In all the model specifications, we took into account the gender, age and TNM stage at diagnosis, and level of treatment hospital of the patients. Results We find that the annual percentage changes of the survival rates increased faster after somewhere around 2013, however, the differential trends were not significant. Results from the Cox multivariate regression analysis suggest that patients who did not participate in the screening program showed significantly lower cancer-specific survival (hazard ratio (HR) = 1.46; 95% confidence interval (CI): 1.12-1.91) and all-causes survival (HR = 1.37; 95% CI: 1.05-1.77), compared to those who did. Among program participants, delayed colonoscopy was associated with poor cancer-specific survival (hazard ratio (HR) = 2.93; 95% confidence interval (CI): 1.64-5.23) and all-causes survival (HR = 3.29; 95% CI: 1.85-5.84). Conclusion Screening participation and high level of colonoscopy compliance can improve the survival of CRC participants.